2022
DOI: 10.11591/ijeecs.v26.i2.pp998-1008
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain integrated multi-agent system for breast cancer diagnosis

Abstract: <span>The integration of multi-agent system and blockchain technology can be beneficial to healthcare applications by providing intelligent data analysis with security. This paper presents an architecture that integrates multi-agent learning system and blockchain technology to support breast cancer diagnosis in a secured manner. The proposed system is based on a parallel hybrid fuzzy logic approach for supporting the prediction of breast cancer disease. The proposed system showed a classification accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Artificial intelligence (AI) techniques are useful in healthcare applications in providing solutions for diagnosis of diseases through the development of software that can analyze like medical experts [1][2][3][4]. The AI and machine learning techniques are being investigated for the medical diagnosis problem by testing its performance on prediction of unknown cases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) techniques are useful in healthcare applications in providing solutions for diagnosis of diseases through the development of software that can analyze like medical experts [1][2][3][4]. The AI and machine learning techniques are being investigated for the medical diagnosis problem by testing its performance on prediction of unknown cases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Reddy et al in [15] used dataset from UCI repository to predicte breast cancer by using many algorithms such as Adaboost, multi-layer perceptron and Stacking classifier, a stacking algorithm has been successful in achieving the best accuracy 99.20%; Ramanath et al [16] they suggested a hybrid system based on fuzzy logic approach to supporting breast cancer prediction illness; the suggested system had shown a 96.49% classification accuracy and Wisconsin data was used. Blockchain has been used to provide security for ensuring the fact that only trusted and reputable agents participate participation in the process of the decision-making.…”
Section: Introductionmentioning
confidence: 99%